Cadangan Kerugian Penurunan Nilai Piutang Perusahaan Perbankan Sebelum dan Setelah Implementasi PSAK 71 - Amrie Firmansyah; Nilam Cahya Ningrum; Putri Meiarta Lubis (STIE Jambatan Bulan, 2022)
Kata Kunci: cadangan kerugian, instrumen keuangan, piutang, perbankan, standar akuntansi keuangan This study examines differences in the value of allowance for impairment losses on loans/credits provided by companies in the banking sub-sector before and after the application of PSAK 71. This study uses a quantitative method approach. The data used in this study is secondary data in the form of data and information from the annual financial statements of 37 banking sub-sector companies listed on the Indonesia Stock Exchange in 2019 and 2020. The research data were obtained from www.idx.co.id. Hypothesis testing was carried out using a paired sample t-test of paired data. This study concludes that applying PSAK 71 causes a difference in the form of an increase in the value of CKPN, which is a component of reducing the value of equity in the financial statements. This research indicates that the Financial Services Authority needs to regulate risk mitigation measures in financial companies due to the implementation of new financial accounting standards that impact changes in the company's assets, capital structure and earnings.